Microbial Flora of Root Canals of Pulpally-infected Teeth: Enterococcus faecalis a Prevalent Species - Gajan, Esrafil Balaei (Tabriz University of Medical Sciences, 2009)
BACKGROUND AND AIMS: The aim of this study was to determine the microorganisms prevalent in the necrotic dental pulp and root canals of unsuccessfully treated teeth. MATERIALS AND METHODS: The present study was conducted on 150 single-rooted teeth of patients referring to a dental clinic. Sampling was performed by placing a sterile paper point in the canal for 60 s. Bacterial samples were evaluated by a microbiological technique specific for anaerobic species, used for isolation and identification of sampled strains. RESULTS: From the 150 samples taken, 101 were from necrotic pulps (primary infection) and 49 were from the teeth with an unsuccessful endodontic treatment (secondary infection). CONCLUSION: Enterococcus faecalis was a prevalent species in the failed root canals evaluated.